KANDUNGAN GIZI KEONG IPONG-IPONG (Fasciolaria salmo) AKIBAT METODE PENGOLAHAN - Sri Purwaningsih; Ella Salamah; Tiza Yunisca Sari (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2012)
Ipong-Ipong (Fasciolaria salmo) snail is a local name of marine mollusc from gastropod class in Cirebon, West Java, which is consumed by public and believed to improve health. The purpose of this research was to find out effect of processing (boiling, steaming, and boiling with 3% salt water) methods on the nutrition content, such as proximate, fatty acids, and cholesterol in F. salmo. The data were analysed using the analysis of variance test (ANOVA). The Duncan test was used to compare means when a significant variation was highlighted by the ANOVA. The results showed nutrition content of fresh F. salmo was: 72.10% water (wet matter basis); protein 62.72% (dry matter basis), ash 7.80% (dry matter basis), cholesterol (0.045%) and 1.71% fat (dry matter basis), monounsaturated fatty acid (11.75%), polyunsaturated fatty acids (7.31%), polyunsaturated fatty acid long chain (5.34%), and saturated fatty acids (long-chain) (4.03%). Acid insoluble ash content was 0.72%. The results of statistical analysis showed that processing method impact the nutritional value of F. salmo. The results of duncan test showed that decreassing content of proximate dan fatty acids caused by steaming method was lower than the boiling and boiling with 3% salt water method. From the research results recommended that the best treatment method is steaming.Keywords: cholesterol, Fasciolaria salmo, fatty acid, processing methods